If in a triangle $ABC$ we have $$1=2\cos A\cos B\cos C+\cos A\cos B+\cos B\cos C+\cos C\cos A\ ,$$ then the triangle will be equilateral triangle.

I tried but except few steps,could not prove it. Putting $A=B=C=\frac{\pi}{3}$ makes both sides equal. How should i prove it?Please help me.

  • $\begingroup$ DO you remember the source of such a nice problem? $\endgroup$ – lab bhattacharjee Jan 7 '16 at 16:45
  • $\begingroup$ Thanks & here is another solution. $\endgroup$ – lab bhattacharjee Jan 7 '16 at 17:50

Observe that the equality fails if one of the $\cos$ is negative. We can assume that triangle is acute. By Jensen and followed by AM-GM inequality: $x = \cos A, y = \cos B, z = \cos C\to x+y+z \leq \dfrac{3}{2}$: $1 = 2xyz + xy+yz+zx \leq 2\cdot \dfrac{(x+y+z)^3}{27}+\dfrac{(x+y+z)^2}{3}\leq \dfrac{2}{27}\cdot \left(\dfrac{3}{2}\right)^3+\dfrac{1}{3}\cdot \left(\dfrac{3}{2}\right)^2=1\to $ equality must occur when $x = y = z \to $ triangle is equilateral.


For brevity write $a=\cos A$, $b=\cos B$, $c=\cos C$. Then we have $$C=\pi-A-B$$ and so $$c=-\cos(A+B)=-ab+\sin A\sin B$$ and so $$(c+ab)^2=(1-a^2)(1-b^2)\ .$$ Expanding, rearranging and using the identity you are given, $$a^2+b^2+c^2=1-2abc=ab+bc+ca\ .$$ Now $$(a-b)^2+(b-c)^2+(c-a)^2=2a^2+2b^2+2c^2-2ab-2bc-2ca$$ and so $$(a-b)^2+(b-c)^2+(c-a)^2=0\ ,$$ which shows that $a,b,c$ are all equal; hence $A,B,C$ are all equal.


As $A+B+C=\pi,\cos(A+B)=\cdots=-\cos C$

and using Prove that $\cos (A + B)\cos (A - B) = {\cos ^2}A - {\sin ^2}B$,

$$2\cos A\cos B\cos C=\cos C[\cos(A-B)+\cos(A+B)]$$




So, the equation reduces to $$\sum(\cos A-\cos B)^2=0$$

Can you take it from here?


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.